2007 40th Annual Hawaii International Conference on System Sciences (HICSS'07) 2007
DOI: 10.1109/hicss.2007.565
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Methodology for Service Construction

Abstract: All large vendors of standard business software have announced to move to service oriented architecture. They claim benefits for their customers with regard to agility and openness. In contrast to the design of software services which has been a focus of research in the computer science community in recent years, the design of enterprise services has not been addressed as much by the information systems research community. This paper outlines a research program on the design of enterprise services. The necessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
0
21
0
3
Order By: Relevance
“…[6,10,34]). Besides the realization through software services several authors also claim a comprehensive understanding of service orientation on business layers to the point of a service oriented enterprise [7,8,27]. The term "enterprise services" is often used in this context.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…[6,10,34]). Besides the realization through software services several authors also claim a comprehensive understanding of service orientation on business layers to the point of a service oriented enterprise [7,8,27]. The term "enterprise services" is often used in this context.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, LEGNER and HEUTSCHI identify the design principles of autonomy and modularity as well as business suitability from existing SOA research on the design of software services [19]. Several authors have presented ideas how enterprise services in particular can be identified and designed [15,24,27] but they still remain very close to the concept of software services that are used in a business context. Therefore they lack a business perspective on service design for a comprehensive EA.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations